LINGUAGEM COMO PRÁTICA SOCIAL - N. Martins, André Ricardo (Cadernos de Linguagem e Sociedade, 2010)
This paper discusses the role of language as social practice. It shows how the introduction of ideology in the study of language has changed the focus on language in recent years. It analyses the specific contribution of Critical Discourse Analysis to the study of language and its relation to social reality. Special attention is given to the relation among language, mass media and democracy.